1985
DOI: 10.1093/infdis/151.6.1093
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of IgM and IgG Responses to Japanese Encephalitis Virus in Human Serum and Cerebrospinal Fluid

Abstract: We measured levels of antibodies to Japanese encephalitis virus (JEV) in serum and in cerebrospinal fluid (CSF) specimens obtained from 32 patients with acute encephalitis by using "antibody-capture" solid-phase enzyme-linked immunoassays specific for IgM or IgG to JEV. The proportions of confirmed cases with IgM to JEV detectable in CSF were 68% (obtained on day 1), 100% (day 7), 96% (day 30), and 72% (day 180). For IgG in CSF the proportions were 47% (day 1), 89% (day 7), 100% (day 30), and 100% (day 180). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(133 citation statements)
references
References 13 publications
6
126
1
Order By: Relevance
“…The results of PCR analysis have not been included in the manuscript because studies show that detection of viruses by isolation or RT-PCR is not sensitive enough for laboratory diagnosis using clinical specimens; this is because of low counts of circulating viruses, rapid clearance of transient viremia soon after the onset of illness, and rapid production of neutralizing antibodies (38,39). For instance, in 90z of the cases, anti-JEV or anti-DV IgM antibodies are detectable in CSF by 4 days and in serum, by 7-9 days following the development of clinical illness (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The results of PCR analysis have not been included in the manuscript because studies show that detection of viruses by isolation or RT-PCR is not sensitive enough for laboratory diagnosis using clinical specimens; this is because of low counts of circulating viruses, rapid clearance of transient viremia soon after the onset of illness, and rapid production of neutralizing antibodies (38,39). For instance, in 90z of the cases, anti-JEV or anti-DV IgM antibodies are detectable in CSF by 4 days and in serum, by 7-9 days following the development of clinical illness (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…High or persisting IgM antibody levels appear to correlate with the severity of the encephalitis and thus, presumably, with the amount of antigenic presentation (Ehrenkrantz et al, 1974;Edelman et aI., 1976). However, Burke et al (1985c) found local synthesis of IgM in the CNS of patients long after recovery from JE, raising the possibility of virus persistence.…”
Section: Immune Responses Of the Central Nervous System: Role Inmentioning
confidence: 99%
“…Antibodies have been measured by standard assays (HI, N, complement-fixation, immunoassays) and have not been characterized by viral protein specificity or employed in cytotoxicity or ADCC assays. Several investigators have described the distribution of antibodies in the IgM and IgG classes in sera from cases of flavivirus encephalitis (Ishii et aI., 1968;Burke et al, 1985c;Monath et aI., 1984). Serum N antibody titers in convalescent sera from cases with overt CNS disease are usually higher than titers in persons who have sustained inapparent infections (Mayer et al, 1976;Chatuverdi et al, 1979), probably reflecting greater viral replication and antigenic stimulation in the former group.…”
Section: Immune Response In Humansmentioning
confidence: 99%
“…Japanese encephalitis (JE) was defined as a febrile illness associated with an altered level of consciousness and the presence of IgM to JEV in the cerebrospinal fluid. 19 Dengue infection was categorized as primary or secondary using the HAI assay results according to the World Health Organization criteria 20 and the standard operating procedure for the reference ELISA. 14 Serum samples.…”
Section: Case Definitionsmentioning
confidence: 99%